Comparative transcriptional profiling of soybean orthologs of arabidopsis trichome developmental genes under salt stress - Suludere, Zekiye; ATAK, ÇİMEN; ÇELİK, ÖZGE (Springer, 233 Spring St, New York, Ny 10013 USA, 2018)
The aim of this study was to determine the ultrastructural changes and regulation of trichome-metabolism-related genes against salt stress in soybean (Glycine max L. Merr.) plants. The 14-day-old Ataem-7 and S04-05 soybean seedlings were subjected to 0, 50, 100, and 150 mM NaCl stress. While the chlorophyll quantities were reduced, the activities of guaiacol peroxidase were increased in both varieties due to increasing NaCl concentrations. In S04-05 soybean variety, trichome densities were increased on both surfaces of the leaves whereas decreases were recorded in Ataem-7 variety at 150 mM NaCl treatment. Stomatal densities were increased on both surfaces of the leaves of both soybean varieties after salinity stress. We also performed a qRT-PCR analysis to evaluate the relative transcription levels of the soybean orthologs of Arabidopsis trichome developmental genes. qRT-PCR analysis demonstrated an induction of the soybean orthologs of GL2 and GL3 genes in soybean plants after 50, 100, and 150 mM NaCl treatments in both varieties. While the expression level of TTG1 ortholog gene was negatively affected in both soybean varieties under different concentrations of salinity, GL1 ortholog gene expression profile differed as a result of changing salt concentrations in both varieties with respect to control plants. It is observed that the regulation of trichome formation differs between two soybean varieties.
Keywords: Salt stress; Trichome density; Stomatal density; Trichome initiation; Glabrous ortholog genes; Soybean; Water-Stress; Antioxidative Enzymes; Lipid-Peroxidation; Gamma-Radiation; Expression; Plants; Tolerant; Responses; Selection; Salinity